Use of information technology on statutory auditors' work: New profiles beyond Spreadsheets' users - Pedrosa, I.; Costa, C.; Laureano, Raul M. S. (2015 10th Iberian Conference on Information Systems and Technologies, CISTI 2015, 2015)
Computer-Assisted Audit Tools and Techniques’ use among auditors has been a research topic on information systems’ acceptance or adoption. Since the late 70, guidelines and suggestions on Computer-Assisted Audit Tools’ use, relating it to auditors’ efficacy and efficiency, have been published by professionals, academics and authoritative bodies. In this paper, the main objective is to define statutory auditors’ profiles on Computer-Assisted Audit Tools’ use. Those profiles emerge from frequent use of CAATs and on the tasks that are being done with CAATs. Indications on further use are presented and discussed. To achieve the objective, an online survey was developed and 110 complete answers were considered. Beyond profiles definition, this paper defines groups of CAATs. This research contributes to enlighten a possible gap between auditors’ needs, available training programmes and software houses’ releases: despite tools’ potential, auditors keep using spreadsheet to execute most of the work. With more focused training, based on, e.g. applied statistics, Data mining and Benford’s Law to fraud detection, this scenario can change in the next years.